PENGARUH PERTUMBUHAN EKONOMI, PENDAPATAN ASLI DAERAH (PAD), DANA ALOKASI UMUM (DAU) DAN DANA ALOKASI KHUSUS (DAK) TERHADAP PENGALOKASIAN ANGGARAN BELANJA MODAL DI KABUPATEN GIANYAR - Septianingrum Diah; Prabawa Gede (Jurnal Ilmiah Manajemen & Bisnis, 2017)
ABSTRACT This study aims to find out the effect of economic growth, local income, general allocation fund, special allocation fund toward capital selling budgeting. Location of study is Gianyar regency. Object in this study as follows: local income, general allocation fund, special allocation fund and gross domestic regional bruto per capita. data analysis technique has been applied in this study is simple regression analysis which beforehand conducted classic assumption test. The result shows that economic growth have positive and significant effect toward capital selling in Gianyar regency, local income have positive and significant effect toward capital selling in Gianyar regency, general allocation fund have positive and significant effect toward capital selling in Gianyar regency, special allocation fund have positive and significant effect toward capital selling in Gianyar regency.